Production of callus mediated gynogenic haploids in winter squash (Cucurbita maxima Duch.) and pumpkin (Cucurbita moschata Duch.) - Ertan Sait KURTAR; Ahmet BALKAYA; Mehtap OZBAKIR OZER (Czech Journal of Genetics and Plant Breeding, 2018)
Although haploids were successfully produced via irradiated pollen technique and anther culture in Cucurbita maxima and Cucurbita moschata, the haploidization efficiency is still low due to genotype dependence. Thus, as an alternative technique, the efficacy of the ovule culture was investigated. Ovules were extracted at different flowering time and then cultured on a solid MS medium supplemented with 2,4-dichlorophenoxyacetic acid (2,4-D), benzylaminopurine (BAP), thidiazuron (TDZ), and naphthaleneacetic acid (NAA) to induce callogenesis and plant regeneration. The gynogenic response was influenced by the combination of plant growth regulators, genotype and culture time. The medium containing of 4.0 mg/l BAP + 0.05 mg/l NAA + 0.1 mg/l TDZ provided the highest response at anthesis time. Plantlets were rooted and elongated on a solid MS medium supplemented with 0.01 mg/l indole-3-acetic acid (IAA) + 1.0 mg/l BAP. The ploidy observations of 122 plants revealed that 70 plants were haploid, 46 plants were diploid and the others were mixoploid.